Postoperative and Long-Term Endocrinologic Complications of Craniopharyngioma - BEREKET, ABDULLAH (KARGER, 2021)
Background: Craniopharyngioma (CP), despite being a malformational tumor of low histological grade, causes considerable morbidity and mortality mostly due to hypothalamo-pituitary dysfunction that is created by tumor itself or its treatment. Summary: Fluid-electrolyte disturbances which range from dehydration to fluid overload and from hypernatremia to hyponatremia are frequently encountered during the acute postoperative period and should be carefully managed to avoid permanent neurological sequelae. Hypopituitarism, increased cardiovascular risk, hypothalamic damage, hypothalamic obesity, visual and neurological deficits, and impaired bone health and cognitive function are the morbidities affecting the well-being of these patients in the long term. Key Messages: Timely and optimal treatment of early postoperative and long-term complications of CP is crucial for preserving quality of life of these patients.
Keywords: Craniopharyngioma; Postoperative complications; Endocrinologic complications; Hyponatremia; Syndrome of inappropriate ADH secretion; Cerebral salt wasting; Obesity; Hypopituitarism